Myeloid-derived suppressor cells in allogeneic hematopoietic stem cell transplantation: A double-edged sword? - Le Blanc, Katarina (Landes Bioscience, 2013)
Accumulating evidence suggests that myeloid-derived suppressor cells (MDSCs) underpin an immunological checkpoint that is activated during inflammation or “inflammatory-like” conditions like cancer. Here, we discuss the identification of MDSCs in patients receiving allogeneic hematopoietic stem cell transplantation and their potential as therapeutic targets or tools for improving the efficacy of this treatment.